Perceptions of gubernatorial authority aspects of the "reality world" of the Philippine provincial governor - Walsh, Thomas P. (Philippine Journal of Public Administration, 1976)
Some sixty-one Philippine provincial governors assessed the pre-martial law political and administrative constraints that impinged on the performance of their gubernatorial functions. The group clamored for: fiscal autonomy through tax reforms, participation in the appointment and supervision of provincial administrative personnel and the PC provincial commander, control of the province's natural resources, and the authority to pardon provincial and municipal prisoners They were anxious and apprehensive over the possibility that 1) local executive authority will be centralized in the Office of the President; 2) members of Congress will assume gubernatorial responsibility; 3) existing inadequacies of their formal authority may be simply maintained; 4) gubernatorial authority may be reversed to pre-1967 Decentralization Law period; or 5) their position may be abolished. These constraints led local officials to resort to "coping mechanisms" which included developing personalized linkages with national officials, maintaining charismatic control over a dependable voting block, or even utilizing extra-legal tactics or their personal wealth for provincial development.